Eine neue Art der Gattung Eusphalerum Kraatz aus Japan (Coleoptera: Staphylinidae: Omaliinae: Eusphalerini). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Eusphalerum eifleri sp. n. from Japan (Honshû), type locality Saijô, Hiroshima-ken, is described, figured and compared with related species. Most likely the new species represents a local endemic.KeywordsColeoptera, Staphylinidae, Omaliinae, Eusphalerum, new species, Japan, Honshû.Nomenclatural Actseifleri Zerche, 2007 (Eusphalerum), spec. n.